2018
DOI: 10.3892/ol.2018.9768
|View full text |Cite
|
Sign up to set email alerts
|

miR‑885‑5p suppresses osteosarcoma proliferation, migration and invasion through regulation of β‑catenin

Abstract: MicroRNAs (miRs) have been reported to serve key roles in cancer. To investigate the function of miR-885-5p in osteosarcoma, the expression levels of miR-885-5p were analyzed in 85 osteosarcoma tissue samples and adjacent non-cancerous tissue samples, using reverse transcription-quantitative polymerase chain reaction analysis. It was demonstrated that miR-885-5p was downregulated in osteosarcoma tissues and cell lines. Notably, the expression level of miR-885-5p was closely associated with tumor size, Tumor-No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…[34] In contrast, miR-885-5p suppressed proliferation, migration and invasion in vitro in osteosarcoma cells, and was downregulated in osteosarcoma patients with low expression levels being associated with a poor prognosis. [35] In our study, miR-885-5p was downregulated in the recurrent tumors, possibly matching the findings in osteosarcoma with low levels of miR-885-5p being associated with more proliferation and a poorer prognosis. Lastly, in our comparison of primary and recurrent WDLPS we did not detect differential expression of the microRNAs that were previously found to be important for sarcomagenesis in WDLPS, such as miR-628 [6], miR-675 [6], miR-26a [8], miR-451 [8] or miR-193b.…”
Section: Discussionsupporting
confidence: 87%
“…[34] In contrast, miR-885-5p suppressed proliferation, migration and invasion in vitro in osteosarcoma cells, and was downregulated in osteosarcoma patients with low expression levels being associated with a poor prognosis. [35] In our study, miR-885-5p was downregulated in the recurrent tumors, possibly matching the findings in osteosarcoma with low levels of miR-885-5p being associated with more proliferation and a poorer prognosis. Lastly, in our comparison of primary and recurrent WDLPS we did not detect differential expression of the microRNAs that were previously found to be important for sarcomagenesis in WDLPS, such as miR-628 [6], miR-675 [6], miR-26a [8], miR-451 [8] or miR-193b.…”
Section: Discussionsupporting
confidence: 87%
“…2,3 The carcinogenesis and tumor progression of thyroid cancer result from varieties of factors, including variation of gene expression and changing activity in signaling pathways. 4,5 Dysregulation of miRNAs has been documented to be implicated in a number of cancers, 8,9 including thyroid cancer. 10 Therefore, the exploration on miRNAs in thyroid cancer is helpful for the identification of potential biological markers for thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…6 Through complementary binding to 3' untranslated regions (3′UTR), miRNAs exhibit suppressive impacts on gene expression. 6 The implication of miRNAs in cancers has been increasingly documented, 8,9 including in thyroid cancer. 6 The implication of miRNAs in cancers has been increasingly documented, 8,9 including in thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have shown that increased levels of miRNA-885-5p in tissues or body fluids can be used as diagnostic markers for tumors and short survival period. [25][26]. Currently, studies involved in target genes of miRNA-885-5p are not enough.…”
Section: Validation Of Prognostic Values Of Mir-885-5p and Mtpn In Ccamentioning
confidence: 99%